A Polygonal Terrain on Southern Martian Polar Cap: Implications for Its Formation Mechanism - Lei Zhang; Yang Lu; Jinhai Zhang (Remote Sensing, 2022)
Polygonal terrains on a Martian southern polar cap have been observed in high-resolution images by the Mars Orbiter Camera. However, their formation mechanism is enigmatic due to the lack of constraints from their geometric and physical properties. Here we proposed a series of recognition procedures on an image of polygonal terrain located at Australe Scopuli taken by a High-Resolution Imaging Science Experiment. Then, we quantitatively analyzed the areas, orientations and polygon edge densities (~0.10 to ~0.06 in different subregions) of the polygonal terrain. Based on the recognition results, three elevation-related subregions can be distinguished according to the distributions of polygon size and orientation. The two side subregions distribute relatively small and relatively large polygons, respectively. The middle subregion can be regarded as an intermediate zone along the slope (~1°). The intermediate zone is squeezed by the surrounding polygons, indicating a possible uplift or subsidence on previous or present Mars. This paper found a possible formation mechanism of the polygonal terrain located at the south pole of Mars, suggesting that polar-ice-cap polygons are formed during the process of lateral sliding gravity-driven plastic creep and the deformation of ice, with the polygon boundaries being reshaped during the alignment at high slopes and partially compressed at low slopes. These properties and possible formation mechanisms could provide more constraints on understanding ancient and/or present climates on Mars.